Genetic polymorphisms in IGF-I and IGFBP-3 are associated with prostate cancer in the Chinese population. - Jian Qian; Hai Zhou; Jiawei Chen; Qi Ding; Qiang Cao; Chao Qin; Pengfei Shao; Pu Li; Hongzhou Cai; Xiaoxin Meng; Xiaobing Ju; Meilin Wang; et al. (PLoS ONE)
Insulin-like growth factor-I (IGF-I) and IGF binding protein-3 (IGFBP-3) are members of the insulin-like growth factor (IGF) family that play important roles in carcinogenesis. We hypothesized that the functional polymorphisms in IGF-I and IGFBP-3 may be associated with the risk of prostate cancer (PCa) in the Chinese population. This hospital-based case-control study included 664 PCa patients and 702 cancer-free controls. Nine SNPs in IGF-I and IGFBP-3 were genotyped using the TaqMan assay. The genetic associations between the pathogenesis and progression of PCa were assessed by logistic regression. We found that the genotype and allele frequency distribution of rs6218, rs35767 and rs5742612 were significantly different when comparing PCa cases to controls (P  = 0.005, 0.005 and 0.020, respectively). In the combined analysis, individuals with 2-6 risk alleles had an elevated risk of PCa compared to those with 0-1 risk alleles. We also found that the association between the combined risk alleles and the risk of PCa appeared stronger in the following subgroups: individuals older than 71 years of age (OR  = 1.41, 95%CI  = 1.05-1.91, P  = 0.020), nonsmokers (OR  = 1.68, 95%CI  = 1.21-2.32, P  = 0.002), nondrinkers (OR  = 1.32, 95%CI  = 1.02-1.61, P  = 0.002), and those with a negative family history of PCa (OR  = 1.28, 95%CI  = 1.02-1.71, P  = 0.022). Our results indicate that the three SNPs (rs6218, rs35767 and rs5742612) and the joint genotypes with 2-6 risk alleles, may contribute to the susceptibility to PCa, but not the progression, in the Chinese population.